The role of the lector in ancient Egyptian society - Forshaw, Roger (Archaeopress Egyptology, 2014)
The lector is first attested during the 2nd Dynasty and is subsequently recognised throughout ancient Egypt history. In previous studies the lector is considered to be one of the categories of the ancient Egyptian priesthood. He is perceived to be responsible for the correct performance of rites, to recite invocations during temple and state ritual, and to carry out recitations and perform ritual actions during private apotropaic magic and funerary rites. Previous treatments of the lector have rarely considered the full extent of his activities, either focusing on specific aspects of his work or making general comments about his role. This present study challenges this selective approach and explores his diverse functions in a wide ranging review of the relevant evidence.